The Influence of Brand Ambassador, Brand Trust and Electronic Word of Mouth on the Purchase Decision of Makeover Cosmetic Products - Sofwatunnisa, Novi; Luthfi Zamakhsyari; Purwidianti, Wida; Hidayah, Arini (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the rapid growth of the cosmetic industry, focusing on MakeOver, a leading brand in Indonesia. The objective is to analyze the impact of Brand Ambassadors, Brand Trust, and Electronic Word of Mouth (eWOM) on consumer purchasing decisions related to MakeOver products. A quantitative approach was employed using questionnaires distributed to 100 respondents. The target population consisted of female students from three universities in Purwokerto: University Muhammadiyah Purwokerto, State Islamic University Prof. K.H. Saifuddin Zuhri, and Wijaya Kusuma University. Purposive sampling was applied, selecting female students who had purchased MakeOver products at least once. Slovin’s formula was used to determine the sample size. Data were analyzed using IBM SPSS Statistics 25. The results reveal that (1) Brand Ambassadors significantly influence purchasing decisions, (2) Brand Trust significantly affects purchasing decisions, (3) eWOM significantly impacts purchasing decisions, and (4) Brand Ambassadors, Brand Trust, and eWOM collectively have a significant effect on consumer purchasing decisions.